(untitled) (Jurnal Bina Praja, 2021)
The study aims to analyze the education and training system and apparatus development at the Regional Financial and Asset Management Agency of Musi Rawas District with the study indicators, namely aspects of education and training of apparatus, career development, or apparatus and placement of human resources using SWOT analysis. Data collection was conducted through interviews, observation, and documentation study methods. The results showed that the Regional Financial and Asset Management Agency of Musi Rawas District is in the prime and steady condition in developing human resources for apparatus. It is really possible to continue increasing growth and achieving maximum progress even though it poses a large enough threat. The strategic recommendation given is the Progressive Strategy, which means that the organization is stable. The human resource development strategy can be carried out progressively towards improving human resources by increasing activities that encourage the development of human resources intensively and continuously. To implement human resource development at the Regional Financial and Asset Management Agency of Musi Rawas District to run well and as needed, it is recommended to determine the priority scale of the education and training. It must be based on the results of the Training Needs Analysis. Then in the implementation of Movements and Promotions carried out based on Career Patterns, Workload Analysis, and Job Analysis.